COLLABORATIVE CREATIVITY IN AD HOC VIRTUAL TEAMS: TESTING AND EVALUATING THE ACCEPTANCE AND USABILITY OF SELECTED CREATIVITY TECHNIQUES IN A VIRTUAL WORKSPACE - Herodek, Anke; Vilmar, Answin (Brazilian Creative Industries Journal, 2021)
Creativity in the context of marketing and as the prerequisite of innovation is a group achievement, not merely a solitary feat. Whereas “group” in the past meant convening in one place, using tools and techniques to be creative together, it recently evolved into meet-ing in virtual places, sometimes with complete strangers, working together to achieve a shared goal, using state-of-the-art information and communication technologies. What stays the same is the need to use creativity techniques, to try to trigger and enhance individual and collaborative creativity, and to gather a greater number of ideas in a short time. This article addresses the acceptance and usability of some of the most popular creativity techniques for virtual ideation in a digital workspace, as well as prominent inhibiting and enhancing factors to virtual creative teamwork. In a laboratory experiment, three selected creativity techniques were tested and the participants were afterwards interviewed about their experiences via an anonymous online survey. The results indicate that creative collaboration is possible and effective also in virtual ad hoc teams. The techniques tested were easily applied and general-ly accepted by the participants and yielded numerous ideas.